If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 2x + -6x + -27 Reorder the terms: y = -27 + 2x + -6x Combine like terms: 2x + -6x = -4x y = -27 + -4x Solving y = -27 + -4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -27 + -4x
| 0.35x+.05(14-x)=.10(49) | | -6+x=-6x+71 | | (2p-2/p)/(10p-10/9p^2) | | x^2+46x-45=0 | | 11u=4u^2-3 | | 8n-10=-5(2+7n)+6n | | 6(7/9+5x)=14/3 | | (12x^3+31x^2-17x-6)/(x+3) | | 5x+6=-5x-4 | | 7(-6x-1)=-469 | | 8b^2-10bc-3c^2= | | 450-2x=3x | | 4(w-3)=5w-21 | | 2x+10=x+21 | | 40+6x=x^2 | | 2(5x-6)=17x+7 | | 6x=144-2x | | 1/5(4x-48)=4x | | 10-(x+8)=5x-4 | | 6v+40=6v-4 | | 7x+3=4x-41 | | 7x+8=7(x-3) | | 9x-3=19-x | | 6(x-3)=3x+45 | | 10x=6x-40 | | 3+x=-5x+57 | | 17x-(9x-2)=42 | | 6x+15=4x+18 | | 4x+58=10x+33 | | x-9=-69-4x | | 7x+3=2x+8 | | -9+4x=7x-1-12 |